The importance of timely ophthalmologic examination in preterm infants at risk of retinopathy occurrence - Knežević Sanja; Stojanović Nadežda; Oros Ana; Knežević Jasmina (Vojnosanitetski Pregled)
Background/Aim. Retinopathy of prematurity (ROP) is a multifactorial disease in premature infants. The aim of this study was to determine the incidence of ROP in children treated at the Center of Neonatology, Pediatric Clinic, Clinical Center in Kragujevac, Serbia. Methods. The study covered all children with birth weight below 2,000 g and/or gestational age below the 37th week, who from June 2006 to December 2009 underwent ophthalmological examination for ROP. The results of fundoscopy were classified in accordance with the International Classification of ROP. The treatment of infants and those with ROP was conducted in accordance with the early treatment of ROP study recommendations. We analyzed gestational age, birth weight and postconceptional age in two groups: healthy infants and those with severe form of ROP. Statistical analysis was performed using the SPSS 16. Results. A total of 478 children met the criteria of screening for ROP. Severe stage of ROP, which required laser treatment, had 102 (21.3%) children. Out of the infants with severe ROP 14 (13.7%) of the infants with APD had aggressive posterior disease, while two (0.4%) remained blind. The differences in the mean values of gestational age between the healthy and the children with severe form of the disease were statistically significant (p < 0.0005). The mean value of gestational age for the healthy children was 33.33 ± 2.28 weeks and for the seek infants 30.66 ± 2.79 weeks. The mean value of the weight in healthy children was 1.981 ± 407 g, and in sick children 1.535 ± 434 g which was statistically significant (p < 0.0005). Multivariate binary logistic regression showed that the occurrence of the disease depends on body weight and gestational age. Conclusion. The incidence of severe forms of ROP was 21.3%. Aggressive form of ROP was present in 13.7% of the children. The cut-off value for body weight was 1.740 g, and for gestational age 32.5 weeks.